CLINICAL SUPERVISION AS A CATALYST FOR EDUCATIONAL IMPROVEMENT - Hifni; Sudadi; Ramdhan, Tri wahyudi (Al-Mudarris: Journal Of Education, 2024)
This study explores the implementation of clinical supervision as a means to enhance teaching quality. Utilizing a qualitative approach and a case study design, data were collected through in-depth interviews, participant observations, and document analysis involving teachers who had experienced clinical supervision, supervisors, and the school principal. The data analysis employed qualitative methods, including open, axial, and selective coding, to identify key themes related to the role of clinical supervision in teacher professional development. The findings reveal that clinical supervision significantly improves teaching quality, particularly in lesson planning, implementation, and evaluation. Teachers reported notable enhancements in their teaching strategies and classroom management following feedback from supervisors. However, the study also uncovered challenges such as time constraints and a lack of sufficient training for supervisors. Despite these challenges, teachers generally held positive perceptions of clinical supervision, recognizing it as an essential tool for their professional growth. In conclusion, this study affirms that clinical supervision is an effective approach to enhancing teaching quality. The study provides recommendations for improving supervisor training and optimizing supervision time to maximize the benefits of the clinical supervision process.